A Visual-Based Project Production Package for Design and Technology Subject Based on Computational Thinking Skills Across-STEM - Ismail R.; Zaman H.B.; Mohammad U.H. (Politeknik Negeri Padang, 2023)
Computational Thinking (CT) is a concept introduced in the problem-solving process and is a systematic way of thinking in computer science and various other disciplines. Awareness to apply CT into education at different curricular levels has started from the beginning of schooling via various contexts and directions. The development of a Visual-Based Project Production Package Model (KHP4) across STEM, using computational thinking skills, in the Reservoir Crop System (ST2) project production process for the Design and Technology (RBT) subject in primary schools aims to improve students' problem-solving and thinking skills by making them be more critical, creative and innovative. The KHP4 also includes the development of RBT learning model and modules. The life cycle model is adapted from the ADDIE l model, which integrates the concept of 'prototyping' based on five (5) main phases: analysis, design, development, implementation, and evaluation with appropriate iteration. This model is based on the COMEL learning model with the practice of interactivity, fun learning, and interesting and motivating learning for students, adding new components and elements. Thus, this paper highlights the evaluation of the Visual-Based Project Production Package Development (KHP4) model in Project Production, which can improve thinking and problem-solving skills based on CT to prepare students for 21st-century learning and instill sustainable development practices in students facing energy transition that is experienced nationally and globally. 2022, Politeknik Negeri Padang. All rights reserved.